A Novel Perspective on the Proactive and Reactive Controls of Executive Function in Chronic Stroke Patients - Yu, Qiuhua; Huang, Xiaomin; Zhang, Baofeng; Li, Zhicheng; Zhang, Tao; Hu, Ziwei; Ding, Minghui; Liang, Zhenwen; Lo, Wai Leung Ambrose (Frontiers in Neurology, 2022)
Objectives To investigate the proactive and reactive control process when executing a complex task in patients with stroke. Proactive control is the preparatory process before the target stimulus, whereas reactive control is an imperative resolution of interference after the target stimulus. Methods In total, 17 patients with chronic stroke and 17 healthy individuals were recruited. The proactive and reactive control of executive function was assessed by the task-switching paradigm and the AX version of the Continuous Performance Task (AX-CPT). The general executive function was assessed by Color Trial Test (CTT) and Stroop Test. The behavioral data of the task-switching paradigm were analyzed by a three-way repeated-measures ANOVA, and the AX-CPT data were analyzed by two-way repeated-measures ANOVA. Results For efficiency scores in the task-switching paradigm, trial (repeat vs. switch) × group (stroke or control group) interaction effect was significant. Post-hoc analysis on trial × group effect showed a significant between-trial difference in accuracy rates in the repeat trial in the control group regardless of 100 or 50% validity. For the AX-CPT, the main effects of condition and group on response time were statistically significant. The interaction effect of condition (AY or BX) × group (stroke or control group) was also significant. Post-hoc analysis for condition × group indicated that the stroke group had a significantly longer response time in the BX condition than the control group and longer completion time in CTT2 and larger word interference for completion time in the Stroop test than the control cohort. Conclusions Post-stroke survivors showed deficits in the performance of proactive control but not in the performance of reactive control. Deficits in proactive control may be related to the impairment of working memory. Interventions that focus on proactive control may result in improved clinical outcomes.